Reducing secondary traumatic stress : skills for sustaining a career in the helping professions - Miller, Brian Cole, 1956- (New York : Routledge, 2021)
"Reducing Secondary Trauma presents a model for supporting emotional well-being in workers who are exposed to the effects of secondary trauma. The book provides helping professionals with a portfolio of skills that support emotion regulation and recovery from secondary trauma exposure and also that enhance the experience of the helping encounter. Each chapter presents evidence-informed skills that allow readers to regulate distressing emotions and to foster increased empathy for those suffering from trauma. Reducing Secondary Trauma goes beyond the usual discussion of burnout to talk in specific terms about what we do about the very real stress that is produced by this work"--
Keywords: Medical personnel -- Job stress; Secondary traumatic stress -- Treatment; Burn out (Psychology) -- Treatment; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD); PSYCHOLOGY / Psychotherapy / General